Puck's Criterion for the tensile response of composite laminates: A numerical approach. (January 2023) - Pai, Anand; Suri, Rishabh; Bhave, Aniket Kunal; Verma, Pranay; N H, Padmaraj
Highlights: Puck's interactive failure criterion applied to non-hybrid laminates. Finite element analysis originating from Representative Volume Element (RVE) stage. Damage Initiation Criteria and Damage Evolution law integrated into the model. Non-hybrid laminates comprising carbon fiber, aramid fiber, Ultra High Molecular Weight Polyethylene (UHMWPE) fabrics investigated. Abstract: Material designers have extensively analyzed, utilizing failure theories, the dependability and service response of composite materials for their intended uses. To increase the precision and accuracy of performance prediction, failure theories have undergone numerous revisions. The current study uses the finite element method to predict the tensile response while also using Puck's failure criterion and the damage evolution law to composite laminates. Five non-hybrid sequences made of paperboard, ultra-high molecular weight polyethylene (UHMWPE), glass fibre, aramid fibre, and carbon fibre have been put through experimental investigation of tensile and three-point bending. The numerical analysis has been carried out using the Material Designer, ACP® and Structural Analysis modules of ANSYS® finite element software. The experimental results have been compared with the numerical results, to arrive at the set of empirical constants for the different materials.